SYNTHESIS OF COBALT FERRITE NANOPARTICLES VIA A SOL-GEL COMBUSTION METHOD - BORTNIC, Rareş-Adrian; GOGA, Firuţa; MESAROŞ, Amalia; NASUI, Mircea; VASILE, Bogdan Ștefan; DUDRIC, Roxana; AVRAM, Alexandra (Studia Universitatis Babeș-Bolyai Chemia, 2016)
This paper presents the synthesis of CoFe2O4 nanoparticles via a sol-gel combustion method. Nanoparticles with the grain size in the range of 20-70 nm were synthesized using hydrated nitrates of cobalt and iron, sucrose and pectin. Sucrose was used as a polycondensation agent for the formation of the gel. The reaction mechanism for the gel formation is discussed in the paper. The addition of pectin facilitated the formation of a hard gel through the drying of the precursor solution at 200oC. Through a thermogravimetric analysis on the gel, the temperature at which the entire organic part has decomposed is concluded. The fine black nanopowder was obtained after a thermal treatment of the gel at a temperature of 700oC. Infrared spectroscopy (FT-IR) highlighted the presence, respectively the absence of organic compounds before and after the thermal treatment. Structural, morphological and magnetic measurements were conducted using X-ray diffraction (XRD), transmission electron microscopy (TEM), vibrating sample magnetometer (VSM).